2018
DOI: 10.1007/s11033-018-4420-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activity of extracts from fruiting bodies and mycelial cultures of Fomitopsis betulina

Abstract: Fomitopsis betulina (Bull.) B.K. Cui, M.L. Han & Y.C. Dai has been used for medicinal purposes for over 5000 years. Numerous studies have confirmed the biological activity of compounds found in this species. The purpose of this study was a comparative analysis of selected groups of metabolites in the extracts from fruiting bodies and mycelial cultures. Phenolic acids (syringic, gallic, p-hydroxybenzoic, 3,4-dihydrophenylacetic), indole compounds (l-tryptophan, 5-hydroxy-l-tryptophan, 5-methyltryptamine), stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…p-Hydroxybenzoic, protocatechuic, and vanillic acid were detected in Fomitopsis pinicola fruiting bodies 24 . Comparative analysis of Fomitopsis betulina fruiting bodies and mycelium showed the presence of syringic, gallic, 5-hydroxybenzoic, and 3,4-dihydrophenylacetic acids 17 . In the present study, the content of phenolic compounds in the F. officinalis mycelium from the in vitro cultures was analyzed for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…p-Hydroxybenzoic, protocatechuic, and vanillic acid were detected in Fomitopsis pinicola fruiting bodies 24 . Comparative analysis of Fomitopsis betulina fruiting bodies and mycelium showed the presence of syringic, gallic, 5-hydroxybenzoic, and 3,4-dihydrophenylacetic acids 17 . In the present study, the content of phenolic compounds in the F. officinalis mycelium from the in vitro cultures was analyzed for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…103.99 and 41.29 mg/100 g DM. respectively 17 . In turn, the ergosterol content in another species of the genus Fomitopsis, Fomitopsis pinicola, was 10,5 mg/100 g d.w. in fruiting bodies 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to a higher concentration of bioactive compounds in fruiting bodies than in mycelia stage. In fact, according to Sulkowska-Ziaja et al, [68] the amounts of bioactive compounds such as polysaccharides, terpenoids, steroids, and phenolic compounds are much lower under the controlled, reproducible conditions of mycelia cultures. Many authors observed that mushroom-derived extracts are particularly effective towards Gram-positive bacteria.…”
Section: Hplc Analysis Of the Fungal Extractsmentioning
confidence: 99%
“…Owing to the fact that mushrooms contain little amounts of lipids (hardly higher than 6–8 % of the dry weight), the studies on these components are the most inadequate. The low lipid content is one of the advantages of mushrooms as nutrients, as they are considered low‐energy functional foods . Interest in lipid substances, especially in fatty acids as main structural lipid elements, is currently expanding.…”
Section: Introductionmentioning
confidence: 99%